(untitled) (Agroindustria, Sociedad y Ambiente, 2019)
This article was developed from a phenomenological hermeneutics research, whose intention was to generate a theoretical approach about the work and knowledge of women in goat management immersed in a vision of sustainable development in Lara state. In-depth interviews were applied to three goat producers women to obtained the information. The analysis and interpretation was processed around categories: goat management, rural productive development of women, and quality of life, from which emerged the senses and meanings attributed by chervines women producers to the reality of the phenomenon of study through the subcategories. For this article, subcategories of greater significance were selected, whose findings were identified as a traditional extensive system of goat management seeking technical institutional support to implement genetic and adaptive models in terms of support for women, by taking equity of gender. These implications for rural productive development, it is assumed in the reflections to highlight the organization of knowledge and entrepreneurial recognition of women in its successful focus on the successful goat productive work intended essentiality to a better quality of life in reason to meet the expectations of survival.